(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2025)
This study aims to examine the impact of animated cartoons on religious, social, and aesthetic values among Libyan children. The study analyzed a sample of 100 children from the city of Sirte using a descriptive analytical approach. Data was collected through a structured questionnaire and analyzed using the SPSS statistical program. The results indicated that animated cartoons play a significant role in enhancing social and aesthetic values, while their influence on religious values may sometimes be negative, especially with prolonged exposure to content that does not align with the cultural and religious environment of Libyan society. The study also found gender differences, with girls being more influenced by religious values compared to boys. Based on these findings, the study recommends the need to regulate children’s media content and promote locally produced animated programs that align with cultural and religious values.